A pilot study of triple therapy with telaprevir, peginterferon and ribavirin for elderly patients with genotype 1 chronic hepatitis C. Issue 10 (16th July 2013) - Hara, Tasuku; Akuta, Norio; Suzuki, Fumitaka; Sezaki, Hitomi; Suzuki, Yoshiyuki; Hosaka, Tetsuya; Kobayashi, Masahiro; Kobayashi, Mariko; Saitoh, Satoshi; Kumada, Hiromitsu
Abstract The prevalence of hepatitis C virus (HCV) infection in elderly patients has been increasing in Japan. However, there are no reports on the safety and efficacy of the triple therapy of telaprevir, peginterferon, and ribavirin for elderly patients with chronic HCV infection. This study evaluated the safety and efficacy of triple therapy [12 weeks of telaprevir 1, 500 mg/day, reduction dose, and 24 weeks of peginterferon and ribavirin] in 18 elderly Japanese patients aged >65 years, with chronic infection with HCV genotype 1b. Four patients received triple therapy with telaprevir 2, 250 mg/day and the other 14 patients received telaprevir 1, 500 mg/day. Sustained virological response‐12 (HCV RNA negativity at 12 weeks after completion of therapy) was 50% (9 of 18 patients); while 4 of 18 (22%) patients discontinued triple therapy due to adverse events (skin rashes, anemia, poor appetite). The dose of telaprevir did not affect HCV RNA clearance rates. Regardless of the dose, 50% of the treated patients achieved sustained virological response‐12, evaluated by intention‐to‐treat analysis. Furthermore, the fall in hemoglobin and the rise in serum creatinine were significantly milder in the telaprevir 1, 500 mg group than the telaprevir 2, 250 mg/day group. Further analysis showed that 67% (6 of 9 elderly patients) with IL28B gene (rs8099917) genotype TT, treated with telaprevir 1, 500 mg, achieved sustained virological response‐12. These results suggest that 24‐week triple therapy with telaprevir 1, 500 mg seems safe and efficacious for elderly Japanese patients infected with HCV genotype 1b. J Med. Virol. 85:1746–1753, 2013. © 2013 Wiley Periodicals, Inc.